2019
DOI: 10.1016/j.jtcvs.2019.03.118
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of the right ventricular outflow tract and the relation to hemodynamics in patients with repaired tetralogy of Fallot

Abstract: Objective: To evaluate the relationship between myocardial histopathology and tissue Doppler imaging (TDI) variables of the right ventricle and postoperative peak systolic right-to-left ventricular pressure ratio (Prv/Plv) in patients undergoing intracardiac repair for tetralogy of Fallot (TOF).Methods: Operatively resected crista supraventricularis muscle specimens from 93 patients undergoing intracardiac repair for TOF, aged 18 months to 26 years (mean, 7.02 AE 5.35 years) were subjected to light microscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The intense inflammation reaction to foreign materials is to blame for the failure of the patch material to cellularize and regenerate effectively. Chowdhury et al [12] reported that hypertrophic, degenerative, and fibrotic changes developed widely in myocardial tissues from RVOT in TOF, and these lesions may reduce the growth potential of cells. In addition, the surgical operation may also damage the myocardium and affect the growth potential.…”
Section: Discussionmentioning
confidence: 99%
“…The intense inflammation reaction to foreign materials is to blame for the failure of the patch material to cellularize and regenerate effectively. Chowdhury et al [12] reported that hypertrophic, degenerative, and fibrotic changes developed widely in myocardial tissues from RVOT in TOF, and these lesions may reduce the growth potential of cells. In addition, the surgical operation may also damage the myocardium and affect the growth potential.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are remarkable clinical differences between TOF patients, which may lead to overconfidence when formulating treatment decisions and predicting prognoses. TOF patients can experience prolonged postoperative recovery even when surgery is successful 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…TOF patients can experience prolonged postoperative recovery even when surgery is successful. 5,6 Reduced pulmonary blood flow (Qp) is the main cause of hemodynamic changes in TOF. Presently, preoperative evaluations of TOF children are performed using the McGoon ratio and the Nakata index but these have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are remarkable clinical differences between TOF patients, which may lead to overconfidence when formulating treatment decisions and predicting prognoses. TOF patients can experience prolonged postoperative recovery even when surgery is successful [5,6].…”
Section: Introductionmentioning
confidence: 99%